Research on pressure fluctuation of coolant with new type of boundary impedance at opening ports of water chamber. (October 2021) - Wang, Xiaoyu; Wang, Haixu; Chen, Yu; Li, Yinglong
Highlights: A new type of impedance model at opening ports has been confirmed. Impedance model combines a one order sound tube with circular piston sound source. Pressure under the vibration of all walls was smaller than single cylinder vibration. Integration of liner and cylinder block might help to eliminate cavitation potential. Abstract: Liner cavitation erosion results from pressure fluctuation of water coolant around cylinders. The characteristics of acoustic field of water chamber are especially important to estimate the potential of liner cavitation. The specialty of water chamber geometry requires a new impedance model of the opening ports, which was simulated by combining a one dimensional sound pipe with piston sound source at infinite plate. The validity of the proposed impedance model has been confirmed by the comparison of attenuation ratio with experiment of actual cylinder block. By changing the clearance between piston and cylinder liner, the influence of cylinder vibration acceleration on water pressure variation was studied, which revealed that the larger clearance results in stronger pressure fluctuation dominated by certain frequencies components. The pressure fluctuation induced by the vibration of whole walls was compared with that induced by the vibration of one cylinder, it revealed that integration of liner and cylinder block may reduce the amplitude of pressure fluctuation.